Digital Natives' Mobile Learning Adoption in terms of UTAUT-2 Model: a Structural Equation Model - Talan, Tarik; Dolan, Yunus; Kalinkara, Yusuf (Univ Malaga, 2024)
This research investigates university students' intentions and behaviors regarding the adoption of mobile learning tools in higher education, with a focus on the Unified Theory of Acceptance and Use of Technology (UTAUT-2) model. A sample of 541 university students from a state university in the Southeastern Anatolia Region of Turkey participated in this study. Structural equation modeling was employed to assess students' mobile learning adoption levels, and statistical analyses were conducted accordingly. The findings indicate a moderate level of mobile learning adoption among the students. The study reveals that students employ various strategies while using mobile tools for learning. Notably, among digital natives, intention to use mobile devices is significantly influenced by habit, hedonic motivation and effort expectancy. Additionally, the study identifies a significant relationship between the use behavior variable and facilitating conditions. The research also examines regulatory effects within the model, demonstrating that age moderates the relationship between habit and use behavior. Furthermore, gender has a moderating effect on the relationship between facilitating conditions and behavioral intention, as well as between hedonic motivation and behavioral intention. Finally, experience moderates the relationship between habit and use behavior, as well as between behavioral intention and use behavior.
Adopción del aprendizaje móvil por parte de los nativos digitales en términos del modelo UTAUT-2: un modelo de ecuaciones estructurales
Keywords: Mobile Learning Adoption; Unified Theory of Acceptance and Use of Technology 2; UTAUT2; Structural Equation Model; Digital Natives